A Conjugate Natural Convection Model for Large Scale Seasonal Thermal Energy Storage Units: Application in Mine Ventilation. (May 2017) - Ghoreishi-Madiseh, Seyed Ali; Amiri, Leyla; Sasmito, Agus P.; Hassani, Ferri P.
Abstract: Ventilation plays an important role in energy demands of mining industry. Using the immense volume of waste rock as thermal energy storage mass to shave seasonal air temperature oscillations is a genuine and practical solution to save on ventilation energy demands. The extensive size and considerable temperature gradients exhibited in such systems point to the importance of buoyancy-driven natural convection heat transfer mechanism. The present study investigates the effect of natural convection and identifies the order of significance of various heat transfer mechanisms. A Conjugate heat transfer and fluid flow model is proposed which includes both the porous rock mass placed in the rock-pit and the air positioned above it. The results of the model are compared and validated against the existing Non-Conjugate models. Using this novel model, significance of forced convection, driven by ventilation fan, and natural convection, driven by buoyancy, are compared. The model is also used to study how design parameters, such as position of intake air trenches and flow rate of fresh air, will affect energy savings.